Konseling Kelompok dengan Pendekatan Behaviouristik untuk Siswa SMP - Erdiyati Erdiyati (Universitas Muria Kudus, 2018)
This article aims to examine the bahavioutristik approach in group counseling situations. The method used is the study of literature by comparing the author's experience during implementing group I school counseling. The result can be found techniques in the bahaviouristic approach that can be developed in the implementation of group counseling for junior high school students